The Use of Politeness Strategies Based on Gender Differences in Harry Potter and the Prisoner of Azkaban Movie: A Socio-Pragmatic Study - Muhammad, Aris Setiawan; Diannurdianti, Ajeng (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2023)
This research focuses on the use of politeness strategies based on gender differences in the movie Harry Potter and the Prisoner of Azkaban. This research aims to (1) determine the types of politeness strategies used by male and female characters in â€œHarry Potter and The Prisoner of Azkabanâ€ movie, (2) discover the differences in politeness strategies used by male and female characters in the movies, and (3) determine the dominant politeness strategies used by male and female characters in the movie. This research used the qualitative method in collecting and analyzing data and the design of the research was a descriptive study. The data source of the research was from the movie of Harry Potter and The Prisoner of Azkaban with 20 male and 8 female characters. The data were collected by watching and transcribing the movie. Furthermore, the researcher analyzed with descriptive qualitative technique. The result of analyzing politeness strategies used based on gender differences showed that 239 utterances used politeness strategies, with males at 173 utterances and females at 66 utterances. The results of the study based on the movie are (1) in the usage of politeness strategies males use the bald on-record 85 (49%) of 173 utterances, positive politeness in 39 (23%) of 173 of utterances, negative politeness in 35 (20%) of 173 utterances, and off-record 14 of (8%) of 173. Whilst, females also use all politeness strategies, there consist of bald on-record 29 (44%) of 66 utterances, positive politeness 22 (33%) of 66 utterances, negative politeness 13 (20%) of 66 utterances, and off- record 2 (3%) of 66 utterances. (2) The differences in politeness strategies used by males and females are in the strategies of notice, exaggerate, hedge, and conventionally indirect. (3) Bald on-strategy is the dominant politeness strategy used, whether by females or males. Males use bald on-record in 85 of 173 utterances and males use 29 of 66 utterances.